2006
DOI: 10.1111/j.1574-6968.2006.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

First genetic characterization of a bacterial β-phenylethylamine biosynthetic enzyme in Enterococcus faecium RM58

Abstract: Enterococcus faecium RM58 produces beta-phenylethylamine and tyramine. A gene from Ent. faecium RM58 coding for a 625 amino-acid residues protein that shows 85% identity to Enterococcus faecalis tyrosine decarboxylase has been expressed in Escherichia coli, resulting in L-phenylalanine and L-tyrosine decarboxylase activities. Both activities were lost when a truncated protein lacking 84 amino acids at its C-terminus was expressed in E. coli. This study constitutes the first genetic characterization of a bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 32 publications
6
64
1
Order By: Relevance
“…Marcobal et al (22) demonstrated that E. faecium and E. faecalis possess a gene coding for an enzyme able to perform L-phenylalanine and L-tyrosine decarboxylation. In our study, this ability was revealed in sausages in the latter period of ripening (30 days), in which 2-phenylethylamine accumulated in detectable amounts (from 2.6 to 19.3 mg/kg DM) in seven runs of the experimental design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Marcobal et al (22) demonstrated that E. faecium and E. faecalis possess a gene coding for an enzyme able to perform L-phenylalanine and L-tyrosine decarboxylation. In our study, this ability was revealed in sausages in the latter period of ripening (30 days), in which 2-phenylethylamine accumulated in detectable amounts (from 2.6 to 19.3 mg/kg DM) in seven runs of the experimental design.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, enterococci are considered among the most active tyrosine decarboxylating bacteria and have also been demonstrated to decarboxylate phenylalanine (6,22,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prokaryotes contain a large array of decarboxylase enzymes, many of which include L-amino acids in their substrate profile (Zheng et al, 2011;Nelson et al, 2015). Indeed, the production of PEA, TYR, and TRP by commensal prokaryotes has been established (Marcobal et al, 2006;Irsfeld et al, 2013;Williams et al, 2014;Yang et al, 2015a), and bacterial production of these compounds was the original basis of Nencki's studies on putrefaction and fermentation (see Grandy, 2007). With TAARs established to be present throughout the body, it is expected that the role of trace amines and their receptors in mediating host-microbiota interactions will become a growing area of interest.…”
Section: Vertebrate Trace Aminesmentioning
confidence: 99%
“…It has been demonstrated that enterococcal tyrosine decarboxylase is also able to decarboxylate phenylalanine, an amino acid structurally related to tyrosine, originating the biogenic amine phenylethylamine (Marcobal et al 2006a). Some authors have demonstrated the simultaneous production of tyramine and phenylethylamine in lactic acid bacteria isolated from wine (Landete et al 2007b).…”
Section: Biogenic Amine Producing Bacteria On Winementioning
confidence: 98%